Characterizing ammonia concentrations and deposition in the United States - Li, Yi, author; Collett, Jeffrey L., advisor; Kreidenweis, Sonia M., committee member; Fischer, Emily, committee member; Ham, Jay, committee member (Colorado State University. Libraries, 2015)
Rapid development of agricultural activities and fossil fuel combustion in the United States led to a great increase of reactive nitrogen (Nr) emissions in the second half of the twentieth century. These emissions have been linked to excess nitrogen (N) deposition in natural ecosystems through dry and wet deposition pathways that can lead to adverse environmental impacts. Furthermore, as precursors of ozone and fine particles, reactive nitrogen species impact regional air quality with resulting effects on human health, visibility, and climate forcing. In this dissertation, ambient concentrations of reactive nitrogen species and their deposition are examined in the Rocky Mountain region and across the country. Particular emphasis is placed on ammonia, a currently unregulated pollutant, despite its important contributions both to nitrogen deposition and fine particle formation. Continuous measurements of the atmospheric trace gases ammonia (NH3) and nitric acid (HNO3) and of fine particle (PM2.5) ammonium (NH4+), nitrate (NO3-) and sulfate (SO42-) were conducted using a denuder/filter system from December 2006 to December 2011 at Boulder, Wyoming, a region of active gas production. The average five year concentrations of NH3, HNO3, NH4+, NO3- and SO42- were 0.17, 0.19, 0.26, 0.32, and 0.48 µg/m3, respectively. Significant seasonal patterns were observed. The concentration of NH3 was higher in the summer than in other seasons, consistent with increased NH3 emissions and a shift in the ammonium nitrate (NH4NO3) equilibrium toward the gas phase at higher temperatures. High HNO3 concentrations were observed both in the summer and the winter. Elevated wintertime HNO3 production appeared to be due to active local photochemistry in a shallow boundary layer over a reflective, snow-covered surface. PM2.5 NH4+ and SO42- concentrations peaked in summer while NO3- concentrations peaked in winter. Cold winter temperatures drove the NH3-HNO3-NH4NO3 equilibrium toward particulate NH4NO3. A lack of NH3, however, frequently resulted in substantial residual gas phase HNO3 even under cold winter conditions. Concentrated agricultural activities and animal feeding operations in the northeastern plains of Colorado represent an important source of atmospheric NH3 that contributes to regional fine particle formation and to nitrogen deposition to sensitive ecosystems in Rocky Mountain National Park (RMNP) located ~80 km to the west. In order to better understand temporal and spatial differences in NH3 concentrations in this source region, weekly concentrations of NH3 were measured at 14 locations during the summers of 2010 to 2014 using Radiello passive NH3 samplers. Weekly average NH3 concentrations ranged from 2.8 µg/m3 to 41.3 µg/m3 with the highest concentrations near large concentrated animal feeding operations (CAFOs). The annual summertime mean NH3 concentrations were stable in this region from 2010 to 2014, providing a baseline against which concentration changes associated with future changes in regional NH3 emissions can be assessed. Vertical profiles of NH3 were also measured on the 300 m Boulder Atmospheric Observatory (BAO) tower throughout 2012. The highest NH3 concentration along the vertical profile was always observed at the 10 m height (annual average concentration is 4.63 µg/m3), decreasing toward the surface (4.35 µg/m3 at 1 m) and toward higher altitudes (1.93 µg/m3 at 300 m). Seasonal changes in the steepness of the vertical concentration gradient were observed, with the sharpest gradients in cooler seasons when thermal inversions restricted vertical mixing of surface-based emissions. The NH3 spatial distributions measured using the passive samplers are compared with NH3 columns retrieved by the Infrared Atmospheric Sounding Interferometer (IASI) satellite and concentrations simulated by the Comprehensive Air quality Model with extensions (CAMx), providing insight into the regional performance of each. U.S. efforts to reduce NOx emissions since the 1970s have substantially reduced nitrate deposition, as evidenced by strongly decreasing trends in long-term wet deposition data. These decreases in nitrate deposition along with increases in wet ammonium deposition have altered the balance between oxidized and reduced nitrogen deposition. Across most of the U.S., wet deposition has evolved from a nitrate dominated situation in the 1980s to an ammonium dominated situation in recent years. Recent measurements of gaseous NH3 concentrations across several regions of the U.S., along with longer-established measurements of gas phase nitric acid, fine particle ammonium and nitrate, and wet deposition of ammonium and nitrate, permit new insight into the balance of oxidized and reduced nitrogen in the total (wet + dry) U.S. reactive nitrogen deposition budget. Utilizing observations from 37 monitoring sites across the U.S., we estimate that reduced nitrogen contributes, on average, approximately 65 percent of the total inorganic N deposition budget. Dry NH3 deposition plays an especially key role in N deposition compared with other N deposition pathways, contributing from 19% to 65% in different regions. With reduced N species now dominating the wet and dry reactive N deposition budgets in much of the country and future estimates suggesting growing ammonia emissions, the U.S. will need to consider ways to actively reduce NH3 emissions if it is to continue progress toward reducing N deposition to sustainable levels defined by ecosystem critical loads.
Keywords: ammonia; atmospheric chemistry; gas/particle partitioning; nitrogen deposition; passive sampler; PM2.5